Safety and Immunogenicity of Heterologous and Homologous 2-Dose Regimens of Adenovirus Serotype 26– and Modified Vaccinia Ankara–Vectored Ebola Vaccines: A Randomized, Controlled Phase 1 Study. (16th September 2020) - Goldstein, Neil; Bockstal, Viki; Bart, Stephan; Luhn, Kerstin; Robinson, Cynthia; Gaddah, Auguste; Callendret, Benoit; Douoguih, Macaya
Abstract: Background: This phase 1 placebo-controlled study assessed the safety and immunogenicity of 2-dose regimens of Ad26.ZEBOV (adenovirus serotype 26 [Ad26]) and MVA-BN-Filo (modified vaccinia Ankara [MVA]) vaccines with booster vaccination at day 360. Methods: Healthy US adults (N = 164) randomized into 10 groups received saline placebo or standard or high doses of Ad26 or MVA in 2-dose regimens at 7-, 14-, 28-, or 56-day intervals; 8 groups received booster Ad26 or MVA vaccinations on day 360. Participants reported solicited and unsolicited reactogenicity; we measured immunoglobulin G binding, neutralizing antibodies and cellular immune responses to Ebola virus glycoprotein. Results: All regimens were well tolerated with no serious vaccine-related adverse events. Heterologous (Ad26, MVA [dose 1, dose 2] or MVA, Ad26) and homologous (Ad26, Ad26) regimens induced humoral and cellular immune responses 21 days after dose 2; responses were higher after heterologous regimens. Booster vaccination elicited anamnestic responses in all participants. Conclusions: Both heterologous and homologous Ad26, MVA Ebola vaccine regimens are well tolerated in healthy adults, regardless of interval or dose level. Heterologous 2-dose Ad26, MVA regimens containing an Ebola virus insert induce strong, durable humoral and cellular immune responses. Immunological memory was rapidly recalled by booster vaccination, suggesting that Ad26 booster doses could be considered for individuals at risk of Ebola infection, who previously received the 2-dose regimen. Abstract : Safety and immunogenicity of 2-dose Ad26.ZEBOV and MVA-BN-Filo vaccine regimens were evaluated in healthy US adults (phase 1 study). Regimens were well tolerated and immunogenic, with higher antibody responses afterose 2 for heterologous regimens with increased dosing intervals.